Preparation of hyperbranched polyester polyol-based urethane acrylates and applications on UV-curable wood coatings - (:unkn) unknown (SPRINGER, 2012)
In the present study, hyperbranched urethane acrylates (UA/HB-PEs) were synthesized by modifying the hydroxyl groups of hyperbranched polyester polyols (HB-PEs). The structure of oligomers were characterized by FTIR and H-1 NMR spectroscopic techniques. Formulations containing UA/HB-PEs, reactive diluents, and photoinitiator were applied onto wood substrates and successfully polymerized under UV-irradiation. The coating performances and thermal properties of UV-cured films were evaluated. The studies on film characteristics reveal that the incorporation of UA/HB-PE afforded coatings with good adhesion and high gloss properties. It is observed that UV-cured coatings originated from [2,2-bis(4-beta-hydroxyethoxy) phenyl propane] (HB-HEPA)- and [2,2-bis(4-beta-hydroxyethoxy) phenyl 6F propane] (HB-HEPFA)-based oligomers possessed better surface and mechanical properties.
Keywords: UV-curing; Hyperbranched polyester polyol; Coating performance; Mechanical properties; MOLECULAR-WEIGHT DISTRIBUTION; TOF MS; POLYMERS; PERFORMANCE; OLIGOMERS